Influence of Nanoparticles Reinforcements on the Mechanical Performance and Tribological Properties of Aluminum 6082 Alloys - AL-OBAIDI, Anwer J.; TARIQ, Abdalameer; DALFI, Hussein (Engineering Transactions, 2022)
This research investigates the effect of using hard ceramic SiC particles on the mechanical and tribological properties of Al6082 alloy. This investigation is performed by mixing various contents of SiC as weight percentages of 0, 1, 2, 3, and 4% with Al6082. Mechanical tests, such as tensile strength and hardness tests, are adopted for this composite (Al6082/SiC) at various contents of the filler (SiC). Besides, the wear test is conducted for the Al6082/SiC composite at various normal loads (10, 15, 20, 25, and 30 N) and sliding distances (200, 400, 600, 800, and 1000 m). Taguchi’s approach is used to create the experimental runs’ matrix. The findings reveal that the mechanical properties improved with increasing the percentage of SiC reinforcement. The tensile strength and Rockwell hardness of Al6082 increased by about 24.6 and 14%, respectively, using 4% of SiC particles. Regarding the tribological behavior, the average wear of Al6082 alloy decreased with increasing the percentage of SiC reinforcement due to higher hardness of reinforcement in Al6082/SiC composite. At the same time, an increase in the normal load and sliding distance led to a decrease in the wear due to increasing plastic deformation at elevated loadings and larger area contacts.